Tour De Singkarak, West Sumatra Event Sustainable Marketing and Tourism - Retnaningtyas Susanti; Fitriana Syahar (International Journal of Tourism, Heritage and Recreation Sport, 2019)
Tour De Singkarak is the name of an international bicycle race competition held by the government of West Sumatra Province since 2009 ago. The event was held as one of the West Sumatra government efforts to promote tourism and attract tourist visits. The central government through the Ministry of Tourism and Creative Economy supports the implementation of this grand event. Every year the number of participants and countries participating in this event increases. One of them is influenced by the increasing nominal prize that can be accepted by the participants. The implementation of TDS events cost not a little, in 2013 the TDS budget reached 4.5 billion Rupiahs. The TDS event was held in West Sumatra to show the world about the tourism potential of West Sumatra. West Sumatra has diverse natural tourism potentials, some of which are part of TDS, among others: Lake Singkarak, Equatorial Bonjol Monument, Harau Valley, Rajo Baso Palace (Pagaruyung), Maninjau Lake (kelok 44), Jam Gadang, Padang Pariaman Beach, Lake Kandis, Lake Kembar, and Beaches on Pesisir Selatan. Most of the TDS stages pass through tourist attractions with extraordinary beauty. Until the last event in 2013, the TDS event had not been considered to provide a continuous contribution to the 3 main aspects, economic, social and environmental in West Sumatra. It is undeniable that this event increases the attractiveness of tourism in West Sumatra in the eyes of the International, but this acquisition is not sustainable and cannot meet the requirements of sustainability. Attractive packaging must be supported by the best quality, TDS events with the international level are expected to be able to provide long-term impact on economic, social and environmental factors.